2016
DOI: 10.1002/chem.201601262
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Construction of Amidines from Arylboronic Acids under Oxidative Conditions

Abstract: A valuable palladium-catalyzed three-component coupling reaction for the synthesis of amidines has been developed. Using arylboronic acids, isocyanides, and anilines as the reactants under oxidative conditions, various amidines were isolated in good yields with good functional group tolerances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 29 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…For example, amide derivatives can undergo CX (Scheme A) or C–X bond activation (Scheme B) . Alternatively, organometallic reagents can react with carbodiimides to form amidines. , More recently, various palladium-based methods have been developed including two-component reactions, in which a C–X bond is activated to form an organopalladium intermediate that then undergoes a reaction with a cyanamide (Scheme C), , and three-component reactions. …”
Section: Introductionmentioning
confidence: 99%
“…For example, amide derivatives can undergo CX (Scheme A) or C–X bond activation (Scheme B) . Alternatively, organometallic reagents can react with carbodiimides to form amidines. , More recently, various palladium-based methods have been developed including two-component reactions, in which a C–X bond is activated to form an organopalladium intermediate that then undergoes a reaction with a cyanamide (Scheme C), , and three-component reactions. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in the field of isocyanide insertions are directed towards further development of these imidoylative Buchwald-Hartwig type cross-couplings. To facilitate this, over the past couple of years there have been multiple reports on the mechanistic aspects of these reactions, allowing chemists to easier predict catalytic behavior and develop more effective catalysts [40][41][42].…”
Section: Cross-couplings With Oxygen or Nitrogen Nucleophilesmentioning
confidence: 99%
“…When it comes to carbon unit, it is often used to construct C–N bonds, C–O bonds, or C–C bonds under palladium-catalyzed conditions . With the deepening of the research on isonitrile, it has been found that the combination of phenylboronic acid and isonitrile can be used as a C–C coupling carrier to construct organic heterocycle molecules in the reaction, from the initial synthesis of simple amides, aryl hydrazine, benzoic acid, and benzophenone, to the synthesis of heterocycles. , The two-phase coupling of phenylboronic acid with isonitrile is commonly used as a benzoyl building block in organic reactions . This method is milder considering the conditions for the preparation of the acyl chloride.…”
Section: Introductionmentioning
confidence: 99%